ANALISIS KADAR ASAM OKSALAT PADA BAYAM BERDASARKAN SUHU PENYAJIAN - Sari, Mayang Fadma (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Spinach is one type of vegetable that contains a myriad of nutrients, but behind the many benefits contained in spinach there is also an inhibitory substance in the form of oxalic acid which is a chemical that can cause kidney stones, not only that excess oxalate in the body will also cause deficiency. or calcium deficiency. The purpose of this study was to determine the levels of oxalic acid in red and green spinach boiled water with different serving temperature variations. This type of research is descriptive, which is research conducted with the aim of describing or describing facts about the population systematically and accurately. With a total sample of 180 grams divided by 90 grams of red spinach and 90 grams of green spinach. The sampling technique used is Simple random sampling with a qualitative examination permanganometric titration method. The variable in this study was the oxalic acid content in red and green spinach based on serving temperature, with univariate data analysis. The results showed that the levels of oxalic acid in red spinach with temperature variations of 80oC, 60oC to 40oC were 16.84mg/l, 19.28mg/l, 20.05mg/l. and green spinach with a temperature variation of 80oC, 60oC to 40oC is 16.50mg/l, 17.68mg/l. 19.39mg/l. In this study, it can be concluded that the content of oxalic acid in boiled water of red spinach and green spinach based on the serving temperature of 80oC, 60oC to 40oC has increased but is still at levels that are safe for consumption.